Characterization of Nepali Solid-state Lamps - Karaliūnas, M.; Vitta, P.; Žukauskas, A.; Zahnd, A.; Bista, D.; Chhetri, B. B.; Updhyaya, M. R. (Elektronika ir Elektrotechnika, 2009)
Two in-door solid-state lamps produced in Nepal for village illumination programs were investigated. The lamps, which are based on white phosphor-conversion LEDs and have different driving circuits (resistive ballast or switching converter), where characterized by measuring the input current, optical output, radiation pattern and chromaticity characteristics as functions of temperature. The variation of the output flux with input voltage was examined. The generated flux, chromaticity, and radiation pattern exhibited stability against temperature variation irrespectively of the driving circuit. The lamp based on the resistive ballast showed a high sensitivity of the output flux to input voltage. Also, for some models of the LEDs used, a noticeable variation of the correlated colour temperature within the viewing angel was observed. Ill. 9, bibl. 10 (in English; summaries in English, Russian and Lithuanian).